Incentive Pay and Firm Productivity: Evidence from China - Zhangfeng Jin; Shiyuan Pan (Global Labor Organization (GLO), 2020)
This study examines the causes and consequences of incentive pay adoption among Chinese manufacturing firms. First, we find that a higher degree of labor scarcity encourages firms to adopt more incentive pay. Second, using an instrumental variables approach, we find that a 10 percentage point increase in the intensity of incentive pay results in 38% higher firm productivity. Third, the average productivity differences between SOEs and non-SOEs decrease by about 65% after controlling differences in incentive pay adoption. Therefore, facilitating incentive pay adoption among firms with better labor endowments (e.g. SOEs) increases productivity while reduces resource misallocation in developing countries.
Keywords: O14; O33; M52; J33; P31; 330; Incentive Pay; Firm Productivity; Labor Scarcity; China; Instrumental Variables